Estimation of the dissipation rate of turbulent kinetic energy: A review. (16th January 2021) - Wang, Guichao; Yang, Fan; Wu, Ke; Ma, Yongfeng; Peng, Cheng; Liu, Tianshu; Wang, Lian-Ping
Highlights: Estimate of turbulent dissipation rate is reviewed. Experimental works are summarized in highlight of spatial/temporal resolution. Data processing methods are compared. Future directions in estimating turbulent dissipation rate are discussed. Abstract: A comprehensive literature review on the estimation of the dissipation rate of turbulent kinetic energy is presented to assess the current state of knowledge available in this area. Experimental techniques (hot wires, LDV, PIV and PTV) reported on the measurements of turbulent dissipation rate have been critically analyzed with respect to the velocity processing methods. Traditional hot wires and LDV are both a point-based measurement technique with high temporal resolution and Taylor's frozen hypothesis is generally required to transfer temporal velocity fluctuations into spatial velocity fluctuations in turbulent flows. Multi probes of hot wires and multi points LDV could be used to measure velocity spatial gradients for a direct calculation of turbulent dissipation rate from its definition. Nevertheless, only PIV and PTV could provide simultaneous measurements of the distribution of turbulent dissipation rate in a turbulent field. These methods all suffer from the deficiency of spatial resolution as velocity measurements are required to resolve down to Kolmogorov scales for a strictly direct calculation of turbulent dissipation rate from fluctuating velocity gradients. To eliminate the necessity of resolving down to Kolmogorov scales, a large eddy simulation analogy and Smagorinsky model could be used for estimating the unresolved small scales, but Smagorinsky constant acts as an adjustment parameter at this stage. Different velocity processing methods are compared in the estimation of turbulent dissipation rate. The estimation of turbulent dissipation rate using structure function, energy spectrum and dimensional analysis methods could reduce the effects of low resolution, but it only provides temporal or spatial mean turbulent dissipation rate. Nevertheless, the field of turbulent dissipation rate, which is not distributed homogeneously, has intermittent spatio-temporal nature. The aim of this paper is to review the developments and limitations of the existing experimental techniques and different calculating methods and identify the future directions in successfully estimating turbulent dissipation rate in turbulent multiphase flows.